Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If $e:=\lim_{n\to\infty} (1 + \frac{1}{n})^n$, prove that $$ \lim_{n\to\infty} \left(1-\frac{1}{n}\right)^{-n} = e $$ without using the property that says: if $\lim_{n\to\infty} a_n = \infty$, $\lim_{n\to\infty} x_n = x$, then $\lim{n\to\infty}(1+\frac{x_n}{a_n})^{a_n} = e^x$...

I've tried rewriting $1-\frac{1}{n}$, and operating $\lim_{n\to\infty}(1-\frac{1}{n})^n = 1 / \lim_{n\to\infty}(1+\frac{1}{n})^n $ but I couldn't prove it. Any hint? Thanks in advance.

share|cite|improve this question
related:… – amWhy Jan 2 '13 at 20:26
I think it matters how you define $e$ in the first place ... – Mark Bennet Jan 2 '13 at 22:34
up vote 7 down vote accepted

\begin{gather} \lim\limits_{n\to\infty}\left(1-\dfrac{1}{n}\right)^{-n}=\lim\limits_{n\to\infty}\left(\dfrac{n-1}{n}\right)^{-n}= \\ =\lim\limits_{n\to\infty}\left(\dfrac{n}{n-1}\right)^{n}=\lim\limits_{n\to\infty}\left[\left(1+\dfrac{1}{n-1}\right)^{n-1}\left(1+\dfrac{1}{n-1}\right)\right]=e \end{gather}

share|cite|improve this answer
Great job. This is the way. – 1015 Jan 2 '13 at 21:02
Nice indeed, but this is not "the way": it is just a way, a nice one, but just one of them. – DonAntonio Jan 2 '13 at 22:05

Note that $$\left(1-\frac{1}{n}\right)\left(1+\frac{1}{n}\right)=1-\frac{1}{n^2}$$

And $$1\geq \left(1-\frac 1{n^2}\right)^n \geq 1-\frac{n}{n^2}$$

The last is an application of Bernoulli's inequality, with $x=-\frac{1}{n^2}$ and $r=n$.

So $(1-\frac 1{n^2})^n\to 1$ and hence $(1-1/n)^n\to e^{-1}$. and $(1-1/n)^{-n}\to e$

share|cite|improve this answer

We have $$\lim_{n\to\infty}\left(1-\frac{1}{n}\right)^{-n}=\lim_{n\to\infty}\left(1+\frac{(-1)}{n}\right)^{n\cdot(-1)}.$$ Now, we can bring the limit inside the $(\cdot)^{-1}$ to have $$\left[\frac{1}{e}\right]^{-1}=e.$$ Observe that I used what you have written so that $$\lim_{n\to\infty}\left(1-\frac{1}{n}\right)^n=\frac{1}{e}.$$ For the proof of the last equality, see @amWhy's comment.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.